2019
DOI: 10.1055/a-1044-2397
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Microvascular Adaptations Following Regular Cold Water Immersion

Abstract: This study investigated the effect of endurance training and regular post-exercise cold water immersion on changes in microvascular function. Nine males performed 3 sessions∙wk-1 of endurance training for 4 weeks. Following each session, participants immersed one leg in a cold water bath (10°C; COLD) for 15 min while the contra-lateral leg served as control (CON). Before and after training, microvascular function of the gastrocnemius was assessed using near-infrared spectroscopy, where 5 min of popliteal arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Microvascular function was assessed by the vascular occlusion test coupled with a NIRS system ( McLay et al., 2016a ; Ihsan et al., 2020b ). This system (Oxymon-MK III, Artinis Medical Systems, Netherlands) provides concentration changes in oxygenated hemoglobin (ΔO 2 Hb), deoxygenated hemoglobin (ΔHHb) and total hemoglobin (ΔtHb ​= ​ΔO 2 Hb ​+ ​ΔHHb).…”
Section: Methodsmentioning
confidence: 99%
“…Microvascular function was assessed by the vascular occlusion test coupled with a NIRS system ( McLay et al., 2016a ; Ihsan et al., 2020b ). This system (Oxymon-MK III, Artinis Medical Systems, Netherlands) provides concentration changes in oxygenated hemoglobin (ΔO 2 Hb), deoxygenated hemoglobin (ΔHHb) and total hemoglobin (ΔtHb ​= ​ΔO 2 Hb ​+ ​ΔHHb).…”
Section: Methodsmentioning
confidence: 99%
“…However, an increase in PGC-1α protein content was not consistently observed in these studies (Ihsan et al, 2015;Aguiar et al, 2016) with only Ihsan et al (2015) reporting an CWI-mediated increase following training. Regardless, complimenting the aforementioned studies showing an increase in VEGF mRNA (Ihsan et al, 2014b;Joo et al, 2016), regular CWI (10-15 min @ 10 • C) incorporated during exercise training lasting 4-12 weeks has been shown to enhance skeletal muscle microvascular function (Ihsan et al, 2020b) and increase skeletal muscle capillarity (D'Souza et al, 2018). Conversely, Broatch et al (2017) found no effect of CWI (15 min @ 10 • C) on molecular markers indicative of mitochondrial development (i.e., mRNA responses, phosphorylation status, and protein abundance) following a single sprint interval training session or following 6 weeks of sprint interval training.…”
Section: Endurance Exercise Adaptation To Post-exercise Cwi: Discrepancy Between Molecular Signaling and Exercise Performancementioning
confidence: 82%
“…Whilst CWI was not conceived as a strategy specifically meant to supplement exercise adaptations, there was substantial interest in examining how recovery-based CWI might influence skeletal muscle adaptations to endurance exercise (Ihsan et al, 2014b(Ihsan et al, , 2015(Ihsan et al, , 2020bAguiar et al, 2016;Joo et al, 2016;Allan et al, , 2019Allan et al, , 2020Broatch et al, 2017). This line of enquiry is likely motivated by work in cell cultures and rodents demonstrating robust increases in mitochondrial markers following exercise and cold exposure with common mechanisms involving PGC-1α.…”
Section: Endurance Exercise Adaptation To Post-exercise Cwi: Discrepancy Between Molecular Signaling and Exercise Performancementioning
confidence: 99%
See 2 more Smart Citations